1984
DOI: 10.1093/jat/8.4.182
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorometric Determination of the Toxic Constituents of Cleistanthus collinus

Abstract: Spectrofluorometric quantitation of a lignan lactone, diphyllin, and its glycosides cleistanthin A and cleistanthin B, the active principles of the poisonous plant Cleistanthus collinus, is reported for the first time. Thin layer chromatographic resolution of the components precedes the fluorometric measurements. The method is highly reproducible and sensitive to 0.1 microgram/mL for diphyllin and to 1 microgram/mL for cleistanthins A and B in ethanol. The technique is employed for the assay of several biospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…In the 1970s a series of phytoconstituents was isolated from the leaves of C. collinus and it includes eargic acid, diphyllin, collinusin, cleistanthin A and cleistanthin B [2] . Later, it was reported that the diphyllin glycoside includes cleistanthins A and B and they are responsible for the C. collinus poisoning [3] which causes severe toxic effects on the cardiac and the respiratory systems in patients. The poisonous effect of C. collinus was observed after 48–72 h of administration.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1970s a series of phytoconstituents was isolated from the leaves of C. collinus and it includes eargic acid, diphyllin, collinusin, cleistanthin A and cleistanthin B [2] . Later, it was reported that the diphyllin glycoside includes cleistanthins A and B and they are responsible for the C. collinus poisoning [3] which causes severe toxic effects on the cardiac and the respiratory systems in patients. The poisonous effect of C. collinus was observed after 48–72 h of administration.…”
Section: Introductionmentioning
confidence: 99%
“…[68–71] Other techniques that have been used for detection of toxin in blood and urine include high performance liquid chromatography (HPLC), spectrophotometry and thin-layer chromatography. [3237397273]…”
Section: Introductionmentioning
confidence: 99%
“…This plant is commonly used as a suicidal and homicidal poison in Southeast Asian countries,[1] and cleistanthins A and B have been reported to be responsible for toxic effects in human beings. [23] Arylnaphthalide lignin glycosides are the major phytoconstituent of the genus Cleistanthus . They are also present in Phyllanthus taxodiifolius, Haplophyllum buxbaumii , and Cleistanthus patulus .…”
Section: Introductionmentioning
confidence: 99%